Economic value analysis of Galanthus sp. in Turkey (Bangladesh Journal of Botany, 2014)
The economic value analysis has been carried out by detecting the production, good and service value functions of Galanthus sp. in Turkey. In the analyses, economical valuation techniques, group comparisons, ecological and socio-cultural valuation criteria had been used. Total flow value for goods and service functions of Galanthus sp. had been calculated as $68/year/unit per Galanthus sp. and the potential flow rate per Galanthus sp. had been estimated at $137/year. The total value of Galanthus sp. had been calculated as $544,000,000/year for annual export of 8 million Galanthus. When the positive added value, which was included in ecological and sociological processes and created by non-pecuniary values and the wealth and heritage value were added, it was easily seen that the economic value of the Galanthus was considerably high. Moreover, it had been determined that especially, the medical source value ($23/year) was a crucial factor among this value. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19748 Bangladesh J. Bot. 43(1): 65-71, 2014 (June)